Interleukin-36 family as a novel regulator of inflammation in the barrier tissues - S. V. Sennikova; A. P. Toptygina (Медицинская иммунология, 2020)
The interleukin-36 (IL-36) family was discerned in the superfamily of interleukin-1 (IL-1) ten years ago. This family includes three isoforms of IL-36α, IL-36β, IL-36γ, which have pro-inflammatory activity and a specific receptor antagonist, IL-36ra, which implements anti-inflammatory function. All of them bind to the same IL-1R6 receptor. The pro-inflammatory isoforms also involve an accessory IL-1RAcP protein into signaling; resulting into conduction of a signal into the cell via the assembling heterodimer receptor. In contrast, IL-36ra inhibits the formation of a heterodimer and blocks the signal transmission. The cytokines of the IL-36 family and appropriate receptors are normally expressed on epithelial cells in barrier tissues such as the respiratory, intestinal tract and skin. Like all cytokines of the IL-1 superfamily, IL-36 is synthesized as inactive form and requires activation, but not due to caspases, but being mediated by neutrophil enzymes, such as cathepsin G, proteinase-3, and elastase, which are constantly present in barrier tissues. In this regard, IL-36 is involved in homeostasis of barrier tissues. Apparently, the IL-36 cytokine system appeared in response to the developing ability of some microorganisms to avoid immune recognition and activation of innate immune response, and, in particular, the IL-1 pro-inflammatory system. An imbalance between the pro- and anti-inflammatory pathways readily causes inflammation in the corresponding tissue. This review discusses participation of cytokines from the IL-36 family in homeostasis of barrier tissues, as well as potential role of the IL-36 family in pathogenesis of bacterial, viral, and fungal skin diseases, atopic dermatitis, autoimmune diseases, such as rheumatoid arthritis, systemic lupus erythematosus, Sjogren's syndrome, ulcerative colitis and Crohn's disease. The role of IL-36 family cytokines in the immunopathogenesis of psoriasis has been well studied. This review is presenting the modern ideas about immune pathogenesis of psoriasis. The special role of cytokines from the IL-36 family was shown both for induction of psoriatic inflammation and evolving a positive feedback loop that supports and enhances the immune component of inflammation, which leads to progression of the disease. Moreover, modern methods of treating psoriasis are discussed, in particular, a possible promising approach to IL-36 blockade, or usage of recombinant IL-36ra for the treatment of psoriatic patients. Experimental studies in this area in mice provide some grounds for optimism.